2011
DOI: 10.1177/1082013210382337
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Nonfried Apple Snacks with Commercially Available Fried Snacks

Abstract: The study was carried out to evaluate the selected quality attributes of a prototype nonfried apple snack produced by application of vacuum impregnation (VI) of maple syrup and vacuum drying. When maple syrup concentration was adjusted to 20-40% in the VI solution, vacuum-dried apple slices are resulted in the greatest textural attributes, whiteness index, and desirable moisture content and water activity. Comparison of the VI-treated, vacuum-dried apple slices with commercially fried apple and potato snacks r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
(24 reference statements)
2
1
0
Order By: Relevance
“…Results showed that each dried fruit snack has a unique spectrum of phenolic compounds. The predominant phenolic compounds in apple snacks are phenolic acids (about 28 mg/100 g DW) and flavonols, in particular isoquercitrin (826.61 ± 58.39 mg/100 g DW), rutin (192.94 ± 34.58 mg/100 g DW), and quercitrin (118.75 ± 24.00 mg/100 g DW) as reported in other studies [42]. Cinnamic acids—especially chlorogenic and p -coumaric acids—are the main phenolics in kiwi and kaki (83.15 ± 2.76 mg/100 g DW and 80.33 ± 1.42 mg/100 g DW, respectively) together with catechins, in particular (−)-epicatechin (20.93 ± 0.48 mg/100 g DW for kiwi and 150.68 ± 0.73 mg/100 g DW for kaki).…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Results showed that each dried fruit snack has a unique spectrum of phenolic compounds. The predominant phenolic compounds in apple snacks are phenolic acids (about 28 mg/100 g DW) and flavonols, in particular isoquercitrin (826.61 ± 58.39 mg/100 g DW), rutin (192.94 ± 34.58 mg/100 g DW), and quercitrin (118.75 ± 24.00 mg/100 g DW) as reported in other studies [42]. Cinnamic acids—especially chlorogenic and p -coumaric acids—are the main phenolics in kiwi and kaki (83.15 ± 2.76 mg/100 g DW and 80.33 ± 1.42 mg/100 g DW, respectively) together with catechins, in particular (−)-epicatechin (20.93 ± 0.48 mg/100 g DW for kiwi and 150.68 ± 0.73 mg/100 g DW for kaki).…”
Section: Resultssupporting
confidence: 73%
“…The sugar pattern is reported in Table 5. Dried apple fruits showed the highest sugar content (from 71 to 83 g/100 g DW), expressed as sum of fructose (36.17 ± 3.13 g/100 g DW), glucose (35.44 ± 3.47 g/100 g DW), and sucrose (5.65 ± 2.88 g/100 g DW) according to previous researches [33,42]. Dried goji snacks showed a sugar level of about 45 g/100 g DW as shown in previous researches [45,50], while dried kaki and kiwi snacks showed small amounts of sugars (15.26 ± 1.26 g/100 g DW and 8.67 ± 1.27 g/100 g DW, respectively) with a clear positive effect on carbohydrate metabolism if compared to traditional dried snacks.…”
Section: Resultssupporting
confidence: 63%
“…The moisture content of the group treated with CL did not show significant differences (P<0.05) in comparison with the group submitted to CC impregnation (Table 1). Moisture values varying between 3.45 and 5.45 % were informed by Joshi et al (2010) working on dried apple snacks. Maximum forces at break were obtained for snacks C L and C C (Table 1).…”
Section: Physicochemical Properties Of Apple Crispy Snacksmentioning
confidence: 99%
“…In addition, research has been done to investigate alternative healthier/natural osmotic solutions (fruit juices, honey, maple syrup, etc.) to traditional ones such as sucrose solutions in order to increase the nutritive/organoleptic value of the OD products (Chauhan, Singh, Singh, Raju, & Bawa, 2011; Gupta, Singh, & Shivhare, 2012; Joshi, Rupasinghe, & Pitts, 2011; Samborska et al, 2019). To improve nutritional quality of mangoes, an inulin pequin oleoresin emulsion was used to enrich mango with polyphenol and inulin during osmotic dehydration, with results suggesting that this emulsion made it possible to incorporate microcapsules of inulin into mango tissue (Jiménez‐Hernández et al, 2017).…”
Section: Introductionmentioning
confidence: 99%